"Kasi" and "bikin"; Two causative strategies in Melayu Tenggara Jauh (Southwest Maluku, Indonesia) - van Engelenhoven, Aone (Wacana, Journal of the Humanities of Indonesia, 2015)
This paper discusses the causative constructions found in Melayu Tenggara Jauh 'Far Southeast Malay' (MTJ), which is used as lingua franca in Southwest Maluku. MTJ encodes causatives by means of MTJ features four periphrastic constructions with the verbs bikin 'do/make' and kasi 'give' that signal whether or not the CAUSER (Kemmer and Verhagen 1994) is involved in or has control over the caused event.